Sensor-Driven Preliminary Wing Ground Plane Sizing Approach and Applications - Ankur S. Patil; Emily J. Arnold (International Journal of Aerospace Engineering)
Structurally integrated antenna arrays provide synergies allowing the integration of large apertures onto airborne platforms. However, the surrounding airframe can greatly impact the performance of the antenna array. This paper presents a sensor-driven preliminary wing ground plane sizing approach to provide insight into the implications of design decisions on payload performance. The improvement of a wing-integrated antenna array that utilizes the wing as a ground plane motivated this study. Relationships for wing span, wing chord, and thickness are derived from extensive parametric electromagnetic simulations based on optimum antenna performance. It is expected that these equations would be used after an initial wing-loading design point has been selected to provide the designer guidance into how various wing parameters might affect the integrated antenna performance.